Efficacy of Antimicrobial Photodynamic Therapy Mediated by Photosensitizers Conjugated with Inorganic Nanoparticles: Systematic Review and Meta-Analysis - Ferrisse, Túlio Morandin [UNESP]; Dias, Luana Mendonça [UNESP]; de Oliveira, Analú Barros [UNESP]; Jordão, Cláudia Carolina [UNESP]; Mima, Ewerton Garcia de Oliveira [UNESP]; Pavarina, Ana Claudia [UNESP] (MDPI, 2022)
Antimicrobial photodynamic therapy (aPDT) is a method that does not seem to promote antimicrobial resistance. Photosensitizers (PS) conjugated with inorganic nanoparticles for the drug-delivery system have the purpose of enhancing the efficacy of aPDT. The present study was to perform a systematic review and meta-analysis of the efficacy of aPDT mediated by PS conjugated with inorganic nanoparticles. The PubMed, Scopus, Web of Science, Science Direct, Cochrane Library, SciELO, and Lilacs databases were searched. OHAT Rob toll was used to assess the risk of bias. A random effect model with an odds ratio (OR) and effect measure was used. Fourteen articles were able to be included in the present review. The most frequent microorganisms evaluated were Staphylococcus aureus and Escherichia coli, and metallic and silica nanoparticles were the most common drug-delivery systems associated with PS. Articles showed biases related to blinding. Significant results were found in aPDT mediated by PS conjugated with inorganic nanoparticles for overall reduction of microorganism cultured in suspension (OR = 0.19 [0.07; 0.67]/p-value = 0.0019), E. coli (OR = 0.08 [0.01; 0.52]/p-value = 0.0081), and for Gram-negative bacteria (OR = 0.12 [0.02; 0.56/p-value = 0.0071). This association approach significantly improved the efficacy in the reduction of microbial cells. However, additional blinding studies evaluating the efficacy of this therapy over microorganisms cultured in biofilm are required.
Keywords: antimicrobial photodynamic therapy; drug-delivery system; Escherichia coli; inorganic nanoparticles; meta-analysis; Staphylococcus aureus; systematic review